LEADERSHIP INVOLVEMENT AND LEADERSHIP SELF-EFFICACY ON ACADEMIC PERFORMANCE AMONG UNDERGRADUATE PHARMACY STUDENTS - Husaini, Nur Eliyah; Mohd Eddy Ratyal, Nur Edlynn Shahirah; Maniam, Sandra; Ali, Aida Azlina (Journal of Islamic, Social, Economics and Development, 2024)
Fostering leadership is essential in pharmacy education, as it is a key step in enhancing professionalism within the field. However, leadership involvement may have an impact on learning performance. The goal of this research was to investigate the association between leadership involvement, leadership self-efficacy and academic performance among undergraduate pharmacy students. Undergraduate pharmacy students were asked to complete an electronic survey. Survey questions were based on cumulative grade point average (CGPA), leadership involvement, Leadership Self-Efficacy Scale (LSS). Descriptive statistics were used to analyze demographic data. The independent t-test and Chi-square test was used to look for associations when comparing variables. Two hundred and ninety-eight (298) students completed the survey. There is a significant difference in leadership self-efficacy (LSE) (p < 0.001) as were Leadership Opportunity (LO), Team Motivation (TM), Innovative Changes (IC) and Ethical Actions and Integrity (EI) (p < 0.001, p < 0.001, p = 0.004, p = 0.001, respectively) between pharmacy students who did and did not participate in leadership activities. It was found that there is no association between leadership involvement and CGPA (p = 0.193). It was also found that there is no association between LSE and CGPA (p = 0.295). There are no associations between the components in LSS (LO, TM, IC and EI) and CGPA (p = 0.787, p = 0.442, p = 0.410, p = 0.250, respectively). Educators may need to focus on other factors that influence academic performance, such as providing individualized support and feedback, promoting active learning strategies, and fostering a positive learning environment.